Akibat Hukum Terhadap Objek Hak Jaminan Fidusia Yang Tidak Dilakukan Pencoretan (Roya) - Paramastuti, Ni Made Ratih Dwitiya; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
This research aims to explain the importance of writing off (roya) fiduciary guarantees. Fiduciary guarantees can be re-established if the object being pledged as collateral has been crossed out on the fiduciary guarantee certificate. The research method used in this research is a normative legal research method with the issue of conflict of norms. Re-registration of a fiduciary guarantee cannot be carried out if it has not been removed. The legal consequences for the fiduciary object if the fiduciary guarantee is not written off after the credit is completed will not be able to register it again as stated expressly in article 20 paragraph (2) of the Regulation of the Minister of Law and Human Rights Number 25 of 2021 which states that if the Applicant does not notify the person of the cancellation of the Fiduciary Guarantee as intended in article 19, Fiduciary Guarantees that have not been written off cannot be re-registered. As a result of not eliminating the collateral status, the owner of the fiduciary object will suffer a great loss because it can no longer be used as collateral for the object he owns. Legal protection for the fiduciary giver for negligence by the recipient of the guarantee in the right not to write off the Fiduciary Giver can take legal action by filing a lawsuit on the basis of an Unlawful Act.